High-corrosion-resistance lithium battery aluminum plastic film and preparation method thereof

By using a multi-layer structure of modified polypropylene inner layer, double-layer modified aluminum foil and nylon outer layer in lithium battery aluminum-plastic film, combined with a polyurethane prepolymer containing disulfide bonds as a binder, the problem of insufficient interface stability and corrosion resistance of existing aluminum-plastic films during high temperature or long-term recycling is solved, and higher corrosion resistance and barrier properties are achieved.

CN120171123AInactive Publication Date: 2025-06-20JIANGSU GONGJU LITHIUM BATTERY MATERIALS CO LTD

Patent Information

Application Number
CN202510637837.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-06-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium battery aluminum-plastic films have problems with insufficient interface stability and corrosion resistance during high temperature or long-term recycling, resulting in decreased bond strength between layers, delamination or microcracks, which in turn accelerates the pitting corrosion of aluminum foil and film layer failure.

Method used

Aluminum-plastic film with a multi-layer structure includes a modified polypropylene inner layer, a double-layer modified aluminum foil and a nylon outer layer. The surface of the modified polypropylene inner layer has a micro-nano structure, and the surface of the double-layer aluminum foil has a gradient corrosion-resistant coating. Multi-layer composite is achieved through a hot pressing composite process using a polyurethane prepolymer containing disulfide bonds as the binder.

Benefits of technology

The corrosion resistance and barrier properties of aluminum-plastic film are significantly improved, the mass loss rate is as low as 0.03%-0.05%, the water vapor transmission rate and oxygen transmission rate are lower than the existing technology, and the peel strength is 6.2-6.8 N/15mm, which effectively solves the problems of interface stress and layering, and improves the safety and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120171123A_ABST
    Figure CN120171123A_ABST
Patent Text Reader

Abstract

The invention discloses a high-corrosion-resistance lithium battery aluminum plastic film and a preparation method thereof. The aluminum plastic film comprises a multi-layer structure from inside to outside: a modified polypropylene inner layer, a first bonding layer, a first modified aluminum foil layer, a second bonding layer, a second modified aluminum foil layer, a third bonding layer and a nylon outer layer. The bonding layer adopts a disulfide bond-containing polyurethane prepolymer, the modified polypropylene inner layer has a micro-nano structure, and the surface of the modified aluminum foil is coated with an Al2O3 and fluorinated graphene gradient corrosion-resistant coating, so that the problems of layering and corrosion of a traditional aluminum-plastic film are solved, and the aluminum-plastic film is suitable for high-energy-density lithium battery packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium battery technology, and particularly to a highly corrosion-resistant aluminum-plastic film for lithium batteries and a preparation method thereof. Background Art

[0002] As an important encapsulation material for soft-pack lithium-ion batteries, the aluminum-plastic film of lithium batteries is responsible for isolating external moisture, oxygen, and electrolyte, ensuring the safety and stability of the battery. Its performance directly affects the service life and reliability of the battery. With the wide application of lithium-ion batteries in new energy vehicles, wearable devices, and energy storage fields, the corrosion resistance, mechanical strength, and high-temperature stability of the aluminum-plastic film have become the focus of research and development. Traditional aluminum-plastic films usually adopt a multi-layer composite structure, including nylon (PA) or polyethylene terephthalate (PET) on the outer layer to provide mechanical protection, an aluminum foil layer in the middle as the main barrier to block penetration, and polypropylene (CPP) or polyethylene (PE) on the inner layer to ensure heat-sealing performance and electrolyte compatibility. In recent years, in response to the requirement of corrosion resistance, researchers have made certain progress by optimizing material formulations, improving the performance of binders, and introducing surface coatings. For example, passivation treatment of the aluminum foil surface (such as chemical conversion film or anodic oxidation) can enhance the anti-electrolyte corrosion ability, while modification of the inner-layer polymer (such as adding fluoride or nano-fillers) improves chemical stability. In addition, some technologies attempt to improve the interfacial bonding force by adjusting the composite process (such as dry or wet composite). These progress have improved the comprehensive performance of the aluminum-plastic film to a certain extent, but there are still many challenges in the face of the requirements of high-energy-density batteries under harsh working conditions.

[0003] However, the multi-layer structure of the existing aluminum-plastic film exposes significant technical limitations during high-temperature or long-term cyclic use, especially in terms of interfacial stability and corrosion resistance. Due to the difference in thermal expansion coefficients of different material layers (such as nylon, aluminum foil, polypropylene), interfacial stress is easily induced during the thermal cycle generated by battery charging and discharging or in a high-temperature environment, resulting in a decrease in the interfacial bonding strength, delamination, or the generation of microcracks. These microcracks not only damage the integrity of the aluminum-plastic film but also provide a penetration path for corrosive substances in the electrolyte (such as HF generated by the decomposition of LiPF6), further accelerating the pitting corrosion of the aluminum foil and the failure of the film layer. Summary of the Invention

[0004] The multi-layer structure of the existing aluminum-plastic film exposes significant technical limitations during high-temperature or long-term cyclic use, especially in terms of interfacial stability and corrosion resistance. Due to the difference in thermal expansion coefficients of different material layers (such as nylon, aluminum foil, polypropylene), interfacial stress is easily induced during the thermal cycle generated by battery charging and discharging or in a high-temperature environment, resulting in a decrease in the interfacial bonding strength, delamination, or the generation of microcracks. These microcracks not only damage the integrity of the aluminum-plastic film but also provide a penetration path for corrosive substances in the electrolyte (such as HF generated by the decomposition of LiPF6), further accelerating the pitting corrosion of the aluminum foil and the failure of the film layer.

[0005] The present application provides a highly corrosion-resistant aluminum-plastic film for lithium batteries, which includes a multi-layer structure from the inside to the outside: a modified polypropylene inner layer, a first adhesive layer, a first modified aluminum foil layer, a second adhesive layer, a second modified aluminum foil layer, a third adhesive layer, and a nylon outer layer; wherein, the first adhesive layer, the second adhesive layer, and the third adhesive layer adopt a polyurethane prepolymer containing disulfide bonds, the surface of the modified polypropylene inner layer has a micro-nano structure, and the surfaces of the first modified aluminum foil layer and the second modified aluminum foil layer have gradient corrosion-resistant coatings.

[0006] As a preferred technical solution of a highly corrosion-resistant aluminum-plastic film for lithium batteries, the polyurethane prepolymer containing disulfide bonds is prepared by the following method: mixing 2,2'-dithiobisethanol and isophorone diisocyanate in a molar ratio of 1:1.0 - 1.5, adding 0.05 - 0.2 wt% of dibutyltin dilaurate catalyst, and reacting at 70°C - 90°C for 3 - 6 hours under the protection of an inert gas to obtain a polyurethane prepolymer containing disulfide bonds.

[0007] As a preferred technical solution of a highly corrosion-resistant aluminum-plastic film for lithium batteries, the gradient corrosion-resistant coating includes an Al2O3 base layer with a thickness of 5 - 10 nm and a fluorinated graphene outer layer with a thickness of 1 - 2 μm. The Al2O3 base layer is formed by plasma-enhanced chemical vapor deposition, and the fluorinated graphene outer layer is formed by a spin-coating process.

[0008] As a preferred technical solution of a highly corrosion-resistant aluminum-plastic film for lithium batteries, the modified polypropylene inner layer contains 5 wt% - 10 wt% of nano-SiO2 and 1 - 3 wt% of silane coupling agent, with a thickness of 20 - 30 μm. Its surface micro-nano structure is a conical array, with a height of 1 - 2 μm and a spacing of 3 - 7 μm.

[0009] As a preferred technical solution of a highly corrosion-resistant aluminum-plastic film for lithium batteries, the surface of the nylon outer layer is coated with a polydimethylsiloxane coating with a thickness of 0.5 - 1 μm, and the contact angle is greater than 120°.

[0010] As a preferred technical solution of a highly corrosion-resistant aluminum-plastic film for lithium batteries, the thicknesses of the first modified aluminum foil layer and the second modified aluminum foil layer are 30 - 50 μm respectively, and the coating amount of the adhesive layer is 2 - 3 g / m 2 , and the peel strength is greater than 5 N / 15mm.

[0011] A method for the highly corrosion-resistant aluminum-plastic film for lithium batteries includes the following steps: Step S1. Prepare a polyurethane prepolymer containing disulfide bonds; Step S2. Perform gradient surface modification on the aluminum foil to form a first modified aluminum foil and a second modified aluminum foil; Step S3. Prepare a modified polypropylene inner layer with micro-nano structures; Step S4. Perform surface treatment on the nylon outer layer; Step S5. Use a disulfide bond-containing polyurethane prepolymer as a binder, and sequentially laminate the modified polypropylene inner layer, the first modified aluminum foil layer, the second modified aluminum foil layer, and the nylon outer layer through a hot pressing and lamination process, and then cure to obtain a highly corrosion-resistant lithium battery aluminum plastic film.

[0012] As a preferred technical solution of the method for the highly corrosion-resistant lithium battery aluminum plastic film, in Step S2, the gradient surface modification includes: depositing a 5-10 nm Al2O3 base layer on the aluminum foil surface by plasma-enhanced chemical vapor deposition, and then spin-coating a 1-2 μm fluorinated graphene layer. The deposition conditions are that the ratio of tetramethylsilane to oxygen is 1:4 - 1:6, the power is 80 - 120 W, and the temperature is 120 - 180 °C.

[0013] As a preferred technical solution of the method for the highly corrosion-resistant lithium battery aluminum plastic film, in Step S3, the preparation of the modified polypropylene inner layer includes: kneading polypropylene with 5-10 wt% nano-SiO2 and 1-3 wt% silane coupling agent, forming a film with a thickness of 20-30 μm through a casting process, and then forming a conical micro-nano array by laser etching. The laser wavelength is 300-400 nm, and the power is 3-7 W.

[0014] As a preferred technical solution of the method for the highly corrosion-resistant lithium battery aluminum plastic film, in Step S5, the conditions of the hot pressing and lamination process are: temperature 120-140 °C, pressure 0.5-1 MPa, time 8-15 seconds; the curing conditions are vacuum curing at 80-100 °C for 10-15 hours.

[0015] The highly corrosion-resistant lithium battery aluminum plastic film and its preparation method provided by the present invention show significant beneficial effects compared with the prior art. Through the double-layer modified aluminum foil (5-10 nm Al2O3 base layer + 1-2 μm fluorinated graphene outer layer) and the modified polypropylene inner layer (5-10 wt% nano-SiO2, 1-3 wt% silane coupling agent, micro-nano structure), the mass loss rate is as low as 0.03% - 0.05%, and the HF corrosion resistance is excellent; the double-layer aluminum foil combined with the gradient corrosion-resistant coating, the water vapor transmission rate (WVTR) is as low as 3.5×10 - 5 g / m 2 ·day, and the oxygen transmission rate (OTR) is as low as 6.0×10 -4 cm 3 / m 2· Excellent barrier performance; the polyurethane prepolymer containing disulfide bonds relieves dynamic stress, with a peel strength of 6.2 - 6.8 N / 15mm, effectively solving the problems of delamination and microcracks during thermal cycling; the optimized hot pressing composite (120 - 140 °C, 0.5 - 1 MPa) and curing annealing (80 - 110 °C) processes ensure high-temperature stability. This aluminum-plastic film is suitable for high-energy-density lithium batteries, meeting the requirements of new energy vehicles, wearable devices and other fields, and greatly improving the battery safety and service life. Description of the Drawings

[0016] Figure 1 Infrared spectrum of the polyurethane prepolymer containing disulfide bonds prepared in Step 1 of Example 1; Detailed Description of the Embodiments

[0017] To make the above objects, features and advantages of the present invention more obvious and understandable, the following detailed description of the specific embodiments of the present invention is made in conjunction with the embodiments of the specification.

[0018] Many specific details are set forth in the following description in order to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein. Those skilled in the art can make similar promotions without departing from the connotation of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed below.

[0019] Secondly, the so-called "one embodiment" or "embodiment" herein refers to a specific feature, structure or characteristic that can be included in at least one implementation manner of the present invention. The "in one embodiment" that appears in different places in this specification does not all refer to the same embodiment, nor is it an embodiment that is separate or selectively mutually exclusive with other embodiments.

[0020] Embodiment Example 1 Example 1 provides a method for a highly corrosion-resistant lithium battery aluminum-plastic film, including the following technical steps: Step 1. Preparation of polyurethane prepolymer containing disulfide bonds: Mix 2,2'-dithiobisethanol with a molecular weight of 1500 g / mol and isophorone diisocyanate (IPDI) in a molar ratio of 1:1.0, and add 0.05 wt% of dibutyltin dilaurate (DBTDL) as a catalyst. Under a nitrogen-protected environment, stir and react at a temperature of 70 °C for 3 hours. After the reaction is completed, cool to room temperature, and then dissolve it in DMF to prepare a 10 wt% solution, finally obtaining a polyurethane prepolymer containing disulfide bonds (SS-PU); Step 2. Gradient surface modification of aluminum foil: Select an aluminum foil with a thickness of 40 μm as the substrate. First, ultrasonically clean it with ethanol and 0.1 mol / L HCl solution and then dry it. Subsequently, through the plasma-enhanced chemical vapor deposition (PECVD) method, with the ratio of tetramethylsilane to oxygen being 1:4, deposit a 5 nm thick Al2O3 layer under the conditions of a power of 80 W and a temperature of 120 °C. Then, spin-coat a 0.5 mg / mL ethanol dispersion of fluorinated graphene (FG, purchased from Nanjing Xianfeng Nano Co., Ltd., fluorine content: ~53%, thickness: 5 - 10 nm, sheet diameter: 4 - 10 μm) to form a 1 μm thick coating. Finally, complete the modification by vacuum baking at 120 °C for 2 hours.

[0021] Step 3. Preparation of the modified polypropylene inner layer: Mix chlorinated polypropylene (CPP, purchased from Jiangsu Ruihe New Materials Co., Ltd., model S350) with a melt index of 3 g / 10min, 5 wt% of nano-SiO2 (particle size 20 nm), and 1 wt% of silane coupling agent KH-570. Conduct mixing in a twin-screw extruder at 180 °C and 100 rpm. Subsequently, prepare a 20 μm thick film through a casting process. Then, perform oxygen plasma treatment on the film (power 50 W, treatment time 30 seconds). Finally, use a 355 nm, 3 W laser etching technology to prepare conical micro-nano arrays with a height of 1 μm and a spacing of 3 μm; Step 4. Surface treatment of the nylon outer layer: Select a 20 μm thick PA6 film as the nylon outer layer material. First, activate its surface through corona treatment at 10 kV and 10 m / min. Then, spray a 0.5 μm thick polydimethylsiloxane (PDMS) and cure it at a temperature of 100 °C for 30 minutes to complete the surface modification of the nylon outer layer; Step 5. Multi-layer composite molding: Uniformly coat the previously prepared SS-PU solution on the bonding surfaces of the modified CPP, modified aluminum foil, and nylon at a coating amount of 2 g / m 2 and dry it at 80 °C for 5 minutes. Subsequently, laminate it in the order of modified CPP / SS-PU / first modified aluminum foil / SS-PU / second modified aluminum foil / SS-PU / nylon, and hot press it at 120 °C and 0.5 MPa for 8 seconds. Finally, vacuum cure it at 80 °C for 10 hours to complete the molding of the multi-layer composite material and obtain a highly corrosion-resistant lithium battery aluminum-plastic film.

[0022] Example 2 Example 2 provides a method for a highly corrosion-resistant lithium battery aluminum-plastic film, including the following technical steps: Step 1. Preparation of disulfide bond-containing polyurethane prepolymer: 2,2'-dithiobisethanol with a molecular weight of 1500 g / mol was mixed with isophorone diisocyanate (IPDI) at a molar ratio of 1:1.2, and 0.1 wt% of dibutyltin dilaurate (DBTDL) was added as a catalyst. Under a nitrogen-protected environment, the mixture was stirred and reacted at 80 °C for 4.5 hours. After the reaction was completed, it was cooled to room temperature and then dissolved in DMF to prepare a 10 wt% solution, finally obtaining a disulfide bond-containing polyurethane prepolymer (SS-PU); Step 2. Gradient surface modification of aluminum foil: Aluminum foil with a thickness of 40 μm was selected as the substrate. First, it was ultrasonically cleaned with ethanol and 0.1 mol / L HCl solution and dried. Subsequently, through the plasma-enhanced chemical vapor deposition (PECVD) method, with the ratio of tetramethylsilane to oxygen being 1:5, a 7.5 nm-thick Al2O3 layer was deposited under the conditions of a power of 100 W and a temperature of 150 °C. Then, a 0.5 mg / mL ethanol dispersion of fluorinated graphene (FG, purchased from Nanjing Xianfeng Nano Co., Ltd., fluorine content: ~53%, thickness: 5 - 10 nm, sheet diameter: 4 - 10 μm) was spin-coated to form a 1.5 μm-thick coating. Finally, it was vacuum baked at 120 °C for 2 hours to complete the modification.

[0023] Step 3. Preparation of modified polypropylene inner layer: Chlorinated polypropylene (CPP, purchased from Jiangsu Ruihe New Materials Co., Ltd., model S350) with a melt index of 3 g / 10 min was mixed with 7.5 wt% of nano-SiO2 (particle size 20 nm) and 2 wt% of silane coupling agent KH-570. It was kneaded in a twin-screw extruder at 180 °C and 100 rpm, and then a 25 μm-thick film was prepared by the casting process. After that, the film was treated with oxygen plasma (power 50 W, treatment time 30 s), and finally, a conical micro-nano array with a height of 1.5 μm and a pitch of 5 μm was prepared using a 355 nm, 3 W laser etching technique; Step 4. Surface treatment of nylon outer layer: A 20 μm-thick PA6 film was selected as the nylon outer layer material. First, its surface was activated by corona treatment at 10 kV and 10 m / min. Then, a 0.75 μm-thick polydimethylsiloxane (PDMS) was sprayed and cured at 100 °C for 30 minutes to complete the surface modification of the nylon outer layer; Step 5. Multilayer composite molding: The previously prepared SS-PU solution was used at 2 g / m 2The coating amount is evenly coated on the bonding surfaces of modified CPP, modified aluminum foil and nylon, and dried at 80 °C for 5 minutes. Subsequently, lamination is carried out in the order of modified CPP / SS-PU / first modified aluminum foil / SS-PU / second modified aluminum foil / SS-PU / nylon, and hot pressing is carried out at 130 °C and 0.75 MPa for 8 seconds. Finally, vacuum curing is carried out at 90 °C for 12.5 hours to complete the molding of the multi-layer composite material, and a highly corrosion-resistant lithium battery aluminum-plastic film is obtained.

[0024] Example 3 Example 3 provides a method for a highly corrosion-resistant lithium battery aluminum-plastic film, including the following technical steps: Step 1. Preparation of polyurethane prepolymer containing disulfide bonds: 2,2'-dithiodiethanol with a molecular weight of 1500 g / mol and isophorone diisocyanate (IPDI) are mixed in a molar ratio of 1:1.5, and 0.2 wt% of dibutyltin dilaurate (DBTDL) is added as a catalyst. Under a nitrogen-protected environment, the mixture is stirred and reacted at a temperature of 90 °C for 6 hours. After the reaction is completed, it is cooled to room temperature, and then dissolved in DMF to prepare a 10 wt% solution, finally obtaining a polyurethane prepolymer containing disulfide bonds (SS-PU); Step 2. Gradient surface modification of aluminum foil: Select an aluminum foil with a thickness of 40 μm as the substrate, first ultrasonically clean and dry it with ethanol and 0.1 mol / L HCl solution, and then through the plasma-enhanced chemical vapor deposition (PECVD) method, with the ratio of tetramethylsilane to oxygen being 1:6, deposit a 10 nm thick Al2O3 layer under the conditions of a power of 120 W and a temperature of 180 °C. Then, spin-coat a 0.5 mg / mL ethanol dispersion of fluorinated graphene (FG, purchased from Nanjing Xianfeng Nano Co., Ltd., fluorine content: ~53%, thickness: 5 - 10 nm, sheet diameter: 4 - 10 μm) to form a 2 μm thick coating, and finally complete the modification by vacuum baking at 120 °C for 2 hours.

[0025] Step 3. Preparation of the modified polypropylene inner layer: Chlorinated polypropylene (CPP, purchased from Jiangsu Ruihe New Materials Co., Ltd., model S350) with a melt index of 3 g / 10 min is mixed with 10 wt% of nano-SiO2 (particle size 20 nm) and 3 wt% of silane coupling agent KH-570, and kneaded in a twin-screw extruder at 180 °C and 100 rpm. Subsequently, a film with a thickness of 30 μm is prepared by the casting process, and then the film is subjected to oxygen plasma treatment (power 50 W, treatment time 30 seconds). Finally, a conical micro-nano array with a height of 2 μm and a pitch of 7 μm is prepared using a 355 nm, 3 W laser etching technology; Step 4. Surface treatment of the nylon outer layer: Select a PA6 film with a thickness of 20 μm as the nylon outer layer material. First, activate its surface by corona treatment at 10 kV and 10 m / min, then spray a 1-μm-thick polydimethylsiloxane (PDMS), and cure it at 100 °C for 30 minutes to complete the surface modification of the nylon outer layer; Step 5. Multi-layer composite molding: Uniformly coat the previously prepared SS-PU solution on the bonding surfaces of the modified CPP, modified aluminum foil, and nylon at a coating amount of 3 g / m 2 and dry it at 80 °C for 5 minutes. Subsequently, laminate it in the order of modified CPP / SS-PU / first modified aluminum foil / SS-PU / second modified aluminum foil / SS-PU / nylon, hot press it at 140 °C and 1 MPa for 15 seconds, and finally vacuum cure it at 100 °C for 15 hours to complete the molding of the multi-layer composite material, obtaining a highly corrosion-resistant lithium battery aluminum-plastic film.

[0026] Example 4 Example 4 provides a method for a highly corrosion-resistant lithium battery aluminum-plastic film, including the following technical steps: Step 1. Preparation of the disulfide bond-containing polyurethane prepolymer: Mix 2,2'-dithiobisethanol with a molecular weight of 1500 g / mol and isophorone diisocyanate (IPDI) in a molar ratio of 1:1.3, and add 0.2 wt% of dibutyltin dilaurate (DBTDL) as a catalyst. Under a nitrogen-protected environment, stir and react at 85 °C for 5 hours. After the reaction is completed, cool it to room temperature, and then dissolve it in DMF to prepare a 10 wt% solution to finally obtain a disulfide bond-containing polyurethane prepolymer (SS-PU); Step 2. Gradient surface modification of the aluminum foil: Select an aluminum foil with a thickness of 40 μm as the substrate. First, ultrasonically clean and dry it with ethanol and 0.1 mol / L HCl solution, and then deposit an 8-nm-thick Al2O3 layer by plasma-enhanced chemical vapor deposition (PECVD) method with a ratio of tetramethylsilane to oxygen of 1:6 under the conditions of a power of 120 W and a temperature of 180 °C. Then, spin-coat a 0.5 mg / mL ethanol dispersion of fluorinated graphene (FG, purchased from Nanjing Xianfeng Nano Co., Ltd., fluorine content: ~53%, thickness: 5 - 10 nm, sheet diameter: 4 - 10 μm) to form a 1.8-μm-thick coating, and finally vacuum bake it at 120 °C for 2 hours to complete the modification.

[0027] Step 3. Preparation of the modified polypropylene inner layer: Chlorinated polypropylene (CPP, with a melt index of 3 g / 10 min, purchased from Jiangsu Ruihe New Materials Co., Ltd., model S350) is mixed with 8 wt% of nano-SiO2 (particle size 20 nm) and 2.5 wt% of silane coupling agent KH-570, and then kneaded in a twin-screw extruder at 180 °C and 100 rpm. Subsequently, a film with a thickness of 28 μm is prepared by a casting process. Then, the film is subjected to oxygen plasma treatment (power 50 W, treatment time 30 s). Finally, a conical micro-nano array with a height of 1.8 μm and a pitch of 6 μm is prepared using a 355 nm, 3 W laser etching technology; Step 4. Surface treatment of the nylon outer layer: A PA6 film with a thickness of 0.8 μm is selected as the nylon outer layer material. First, its surface is activated by corona treatment at 10 kV and 10 m / min. Then, a 0.8-μm-thick layer of polydimethylsiloxane (PDMS) is sprayed and cured at 100 °C for 30 minutes to complete the surface modification of the nylon outer layer; Step 5. Multi-layer composite molding: The previously prepared SS-PU solution is uniformly coated on the bonding surfaces of the modified CPP, modified aluminum foil, and nylon at a coating amount of 2.8 g / m 2 and dried at 80 °C for 5 minutes. Subsequently, lamination is carried out in the order of modified CPP / SS-PU / first modified aluminum foil / SS-PU / second modified aluminum foil / SS-PU / nylon, hot-pressed at 135 °C and 0.8 MPa for 10 s, and finally vacuum-cured at 95 °C for 14 hours to complete the molding of the multi-layer composite material, obtaining a highly corrosion-resistant lithium battery aluminum-plastic film.

[0028] Control example Control example 1 The difference between this control example 1 and Example 1 lies in Step 5. Multi-layer composite molding: The previously prepared SS-PU solution is uniformly coated on the bonding surfaces of the modified CPP, modified aluminum foil, and nylon at a coating amount of 2 g / m 2 and dried at 80 °C for 5 minutes. Subsequently, lamination is carried out in the order of modified CPP / SS-PU / modified aluminum foil / SS-PU nylon, hot-pressed at 120 °C and 0.5 MPa for 8 s, and finally vacuum-cured at 80 °C for 10 hours to complete the molding of the multi-layer composite material, obtaining a highly corrosion-resistant lithium battery aluminum-plastic film.

[0029] Control example 2 The difference between this control example 2 and Example 1 is that unmodified aluminum foil is used to replace the modified aluminum foil.

[0030] Control example 3 The difference between this comparative example and Example 1 is that the polypropylene inner layer does not contain nano-SiO2 and silane coupling agent, and has no micro-nano structure.

[0031] Comparative Example 4 The difference between this comparative example and Example 1 is that the binder is a traditional polyurethane prepolymer (purchased from Hubei Chengfeng Chemical Co., Ltd., CAS: 103837-45-2, content greater than 99%, without disulfide bonds).

[0032] Performance detection test Corrosion resistance test: Cut the aluminum-plastic film sample into 50 mm×50 mm, weigh and record the initial mass (accurate to 0.1 mg), and then place it in an electrolyte simulation solution containing 0.1 mol / L HF (prepared by dissolving LiPF6 in a mixed solvent of EC / DMC = 1:1), and soak it in a constant temperature oven at 60°C for 168 hours. After soaking, rinse the sample with deionized water and dry it at 80°C for 2 hours, and weigh it again to calculate the mass loss rate (mass loss rate = (initial mass - final mass) / initial mass × 100%).

[0033] Barrier property test: Use a water vapor transmission rate tester (such as MOCON Permatran-W) and an oxygen transmission rate tester (such as MOCON Ox-Tran) for testing. Cut the aluminum-plastic film sample into a circle with a diameter of 100 mm, fix it in the test equipment, and test the water vapor transmission rate (WVTR) under the conditions of 38°C and 90% relative humidity, record the transmission amount within 24 hours, and the unit is g / m 2 ·day; at the same time, test the oxygen transmission rate (OTR) at 23°C and 0% relative humidity, record the transmission amount within 24 hours, and the unit is cm 3 / m 2 ·day Interface strength test: Cut the aluminum-plastic film sample into strips of 15mm×100 mm, and use a universal tensile testing machine (such as Instron 5967) to conduct a 180° peel strength test. Fix one end of the sample and stretch the other end at a speed of 50 mm / min, record the maximum peel force, and the unit is N / 15mm. Test 5 samples and take the average value to ensure that the peel strength > 5 N / 15mm.

[0034] Table 1 Combined with Example 1 and Figure 1 It can be seen that the functional groups are analyzed as follows: 3300 cm -1 (N-H stretching), 1700 cm -1 (C=O stretching), 1530 cm -1The negative peak of (N-H bending) confirms the presence of urethane bond (-NHCOO-); 2960 cm -1 (CH3 stretching), 2900 cm -1 (CH2 stretching), 1460 cm -1 (CH2 shearing), 1375 cm -1 (CH3 bending), 1365 cm -1 The negative peak of (CH2 rocking) reflects the alkyl structure; 1250 cm -1 (C-N stretching), 1100 cm -1 (C-C stretching) indicates the integrity of the molecular skeleton; 675 cm -1 (C-S stretching) is the characteristic of thioether bond. The disulfide bond (-S-S-) shows a negative peak at 525 cm -1 proving its retention and supporting the self-healing performance of the aluminum-plastic film. There is no peak at 2260 cm -1 (-NCO) and 3400 cm -1 (-OH) in the spectrum, indicating that the reaction of 2,2'-dithiobisethanol with IPDI is complete, generating the target polyurethane structure and meeting the requirements of corrosion resistance performance.

[0035] Combining Examples 1 to 4 and Table 1, it can be seen that the performance ranges of Examples 1 to 4 in terms of corrosion resistance, barrier property, and interfacial strength are as follows: the mass loss rate ranges from 0.03% to 0.05%, the water vapor transmission rate (WVTR) ranges from 3.5×10 -5 to 4.5×10 -5 g / m 2 ·day, the oxygen transmission rate (OTR) ranges from 6.0×10 -4 to 7.0×10 -4 cm 3 / m 2 ·day, and the peel strength ranges from 6.2 to 6.8 N / 15mm. These data indicate that the aluminum-plastic film of the present invention exhibits excellent corrosion resistance, barrier property, and interfacial strength through the synergistic effect of the double-layer modified aluminum foil, the modified polypropylene inner layer, and the polyurethane binder containing disulfide bonds.

[0036] Combining Example 1, Comparative Example 1, and Table 1, it can be seen that Example 1 is significantly superior to Comparative Example 1 in terms of corrosion resistance, barrier property, and interfacial strength. The mass loss rate of Example 1 is 0.05%, which is much lower than 0.12% of Comparative Example 1; the water vapor transmission rate (WVTR) is 4.5×10 -5 g / m 2 ·day, while that of Comparative Example 1 is 8.0×10 -5 g / m 2 ·day; the oxygen transmission rate (OTR) is 7.0×10-4 cm 3 / m 2 ·day, and that of Comparative Example 1 was 1.2×10 -3 cm 3 / m 2 ·day; the peel strength was 6.2 N / 15 mm, higher than 5.8 N / 15 mm of Comparative Example 1. Example 1 adopted a double-layer modified aluminum foil, which provided stronger barrier properties and HF corrosion resistance compared with the single-layer aluminum foil structure of Comparative Example 1; the modified polypropylene inner layer and the disulfide bond-containing polyurethane binder (SS-PU) enhanced chemical stability and interfacial bonding force, and relieved interfacial stress; the double-layer structure formed a more uniform interface during hot pressing and curing processes, further improving the performance.

[0037] Combining Example 1, Comparative Example 2 and Table 1, it can be seen that Example 1 was significantly superior to Comparative Example 2 in terms of corrosion resistance, barrier properties and interfacial strength. The mass loss rate of Example 1 was 0.05%, far lower than 0.20% of Comparative Example 2; the water vapor transmission rate (WVTR) was 4.5×10 -5 g / m 2 ·day, lower than 5.0×10 -5 g / m 2 ·day of Comparative Example 2; the oxygen transmission rate (OTR) was 7.0×10 -4 cm 3 / m 2 ·day, lower than 7.5×10 -4 cm 3 / m 2 ·day of Comparative Example 2; the peel strength was 6.2 N / 15 mm, higher than 6.0 N / 15 mm of Comparative Example 2. Example 1 adopted a double-layer modified aluminum foil, while Comparative Example 2 used an unmodified aluminum foil, resulting in a significant decrease in HF corrosion resistance due to the lack of protection of the gradient corrosion-resistant coating; the modified polypropylene inner layer and the disulfide bond-containing polyurethane binder (SS-PU) of Example 1 enhanced the barrier properties and interfacial bonding force through chemical stability and dynamic stress relief mechanisms, while the surface energy of the unmodified aluminum foil of Comparative Example 2 was relatively low, limiting the bonding effect; the double-layer structure of Example 1 formed a denser interface during hot pressing and curing processes, further improving the performance. Example 1 significantly improved corrosion resistance, barrier properties and interfacial strength through the double-layer modified aluminum foil and the synergistic modification system, solved the corrosion and penetration problems of the unmodified aluminum foil, and demonstrated excellent comprehensive performance.

[0038] Combining Example 1, Comparative Example 3 and Table 1, it can be seen that Example 1 was significantly superior to Comparative Example 3 in terms of corrosion resistance, barrier properties and interfacial strength. The mass loss rate of Example 1 was 0.05%, far lower than 0.15% of Comparative Example 3; the water vapor transmission rate (WVTR) was 4.5×10-5 g / m 2 ·day, lower than 6.5×10 -5 g / m 2 ·day of Comparative Example 3; the oxygen transmission rate (OTR) is 7.0×10 -4 cm 3 / m 2 ·day, lower than 9.0×10 -4 cm 3 / m 2 ·day of Comparative Example 3; the peel strength is 6.2 N / 15mm, higher than 5.5 N / 15mm of Comparative Example 3. The reason for the superior performance is as follows: 5wt% of nano-SiO2 and 1wt% of KH-570 are added to the modified polypropylene inner layer of Example 1, and a micro-nano structure (height 1μm, spacing 3μm) is formed by laser etching, significantly improving the chemical stability and liquid repellency. While the polypropylene inner layer of Comparative Example 3 is unmodified and has no micro-nano structure, resulting in increased electrolyte penetration and corrosion; Example 1 uses a double-layer modified aluminum foil (each layer 40 μm, with a 5 nm Al2O3 and 1μm graphene fluoride coating) and a disulfide bond-containing polyurethane binder (SS-PU), enhancing the barrier property and interfacial bonding force through a gradient corrosion-resistant coating and a dynamic stress relief mechanism. Although Comparative Example 3 has a modified aluminum foil, the weakness of the unmodified inner layer limits the overall performance; the hot pressing and lamination (120°C, 0.5 MPa, 8 seconds) and curing (80°C, 10 hours) processes of Example 1 optimize the interfacial bonding. While in Comparative Example 3, due to the lower surface energy of the inner layer, the bonding effect is poor. In summary, through the synergistic effect of the modified polypropylene inner layer and the double-layer modified aluminum foil in Example 1, the corrosion resistance, barrier property, and interfacial strength are significantly improved, solving the problems of corrosion and delamination of the unmodified inner layer, and demonstrating excellent comprehensive performance Combined with the experimental data of Example 1, Comparative Example 4, and Table 1, it can be seen that Example 1 is significantly superior to Comparative Example 4 in terms of corrosion resistance, barrier property, and interfacial strength. The mass loss rate of Example 1 is 0.05%, much lower than 0.10% of Comparative Example 4; the water vapor transmission rate (WVTR) is 4.5×10 -5 g / m 2 ·day, lower than 5.5×10 -5 g / m 2 ·day of Comparative Example 4; the oxygen transmission rate (OTR) is 7.0×10 -4 cm 3 / m 2 ·day, lower than 8.0×10 -4 cm 3 / m 2·day; The peel strength was 6.2 N / 15mm, significantly higher than 4.8 N / 15mm of Comparative Example 4, and Comparative Example 4 did not reach the target value (>5 N / 15mm). The reason for the superior performance is as follows: In Example 1, a disulfide-containing polyurethane prepolymer (SS-PU, molar ratio 1:1.0, 0.05wt% DBTDL, reacted at 70°C for 3 hours) was used as the binder. Its disulfide bond (-S-S-) effectively alleviated the interfacial stress through the dynamic fracture-recombination mechanism, enhancing the bonding stability and corrosion resistance. In contrast, Comparative Example 4 used a traditional polyurethane binder (without disulfide bonds), resulting in greater interfacial stress, insufficient peel strength, and increased corrosion; The double-layer modified aluminum foil in Example 1 (40 μm for each layer, with 5 nm Al2O3 and 1 μm graphene fluoride coating) and the modified polypropylene inner layer (5wt% nano-SiO2, 1wt% KH-570, micro-nano structure height 1 μm, spacing 3 μm) synergistically improved the barrier property and chemical stability. Although Comparative Example 4 had the same modified aluminum foil and inner layer, the weak interfacial bonding of the traditional binder limited the overall performance; The hot pressing composite (120°C, 0.5 MPa, 8 seconds) and curing (80°C, 10 hours) processes in Example 1 further optimized the interfacial bonding. Due to the insufficient performance of the binder in Comparative Example 4, the interfacial strength was poor. In summary, through the synergistic effect of the disulfide-containing polyurethane binder and the modified materials in Example 1, the corrosion resistance, barrier property, and interfacial strength were significantly improved, solving the delamination and corrosion problems of traditional binders and demonstrating excellent comprehensive performance.

[0039] The above are only the preferred embodiments of the present invention and are not used to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A highly corrosion-resistant lithium battery aluminum-plastic film, characterized in that: The invention comprises a multilayer structure from inside to outside: a modified polypropylene inner layer, a first adhesive layer, a first modified aluminum foil layer, a second adhesive layer, a second modified aluminum foil layer, a third adhesive layer and a nylon outer layer; wherein the first adhesive layer, the second adhesive layer and the third adhesive layer are made of a polyurethane prepolymer containing a disulfide bond, the surface of the modified polypropylene inner layer has a micro-nano structure, and the surfaces of the first modified aluminum foil layer and the second modified aluminum foil layer have a gradient corrosion-resistant coating; the gradient corrosion-resistant coating comprises an Al2O3 base layer with a thickness of 5-10 nm and a fluorinated graphene outer layer with a thickness of 1-2 μm, the Al2O3 base layer is formed by plasma enhanced chemical vapor deposition, and the fluorinated graphene outer layer is formed by a spin coating process.

2. The aluminum-plastic film according to claim 1, characterized in that: The polyurethane prepolymer containing disulfide bonds is prepared by the following method: 2,2'-dithiodiethanol and isophorone diisocyanate are mixed at a molar ratio of 1:1.0-1.5, 0.05-0.2wt% of dibutyltin dilaurate catalyst is added, and the mixture is reacted at 70°C-90°C for 3-6 hours under the protection of inert gas to obtain a polyurethane prepolymer containing disulfide bonds.

3. The aluminum-plastic film according to claim 1, characterized in that: The modified polypropylene inner layer contains 5wt%-10wt% of nano-SiO2 and 1-3wt% of silane coupling agent, with a thickness of 20-30 μm. Its surface micro-nano structure is a cone array with a height of 1-2 μm and a spacing of 3-7 μm.

4. The aluminum-plastic film according to claim 1, characterized in that: The surface of the nylon outer layer is coated with a polydimethylsiloxane coating with a thickness of 0.5-1 μm, and the contact angle is greater than 120°.

5. The aluminum-plastic film according to claim 1, characterized in that: The thickness of the first modified aluminum foil layer and the second modified aluminum foil layer are 30-50 μm respectively, and the coating amount of the bonding layer is 2-3 g / m 2 , peel strength is greater than 5 N / 15mm.

6. A method for preparing the highly corrosion-resistant lithium battery aluminum-plastic film according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1. preparing a polyurethane prepolymer containing a disulfide bond; Step S2. performing gradient surface modification on the aluminum foil to form a first modified aluminum foil and a second modified aluminum foil; Step S3. preparing a modified polypropylene inner layer having a micro-nano structure; Step S4. performing surface treatment on the nylon outer layer; Step S5. Using a disulfide bond-containing polyurethane prepolymer as a binder, the modified polypropylene inner layer, the first modified aluminum foil layer, the second modified aluminum foil layer and the nylon outer layer are compounded in sequence through a hot pressing composite process, and then cured to obtain a highly corrosion-resistant lithium battery aluminum-plastic film.

7. The method according to claim 6, characterized in that In step S2, the gradient surface modification includes: using plasma enhanced chemical vapor deposition to deposit a 5-10 nm Al2O3 base layer on the surface of the aluminum foil, and then spin coating a 1-2 μm fluorinated graphene layer, the deposition conditions are tetramethylsilane and oxygen ratio 1:4-1:6, power 80-120 W, temperature 120-180 ° C.

8. The method according to claim 6, characterized in that In step S3, the preparation of the modified polypropylene inner layer includes: mixing polypropylene with 5-10wt% nano-SiO2 and 1-3wt% silane coupling agent, forming a film with a thickness of 20-30μm by a casting process, and then using laser etching to form a conical micro-nano array, with a laser wavelength of 300-400 nm and a power of 3-7 W.

9. The method according to claim 6, characterized in that In step S5, the conditions of the hot pressing composite process are: temperature 120-140° C., pressure 0.5-1 MPa, time 8-15 seconds; the curing conditions are 80-100° C. vacuum curing for 10-15 hours.

Citation Information

Patent Citations

  • Method for constructing micro-nano structure on polypropylene surface

    CN102101358A

  • Surface-oleophobic aluminum plastic film for packaging lithium battery and preparation process of surface-oleophobic aluminum plastic film

    CN104466039A

  • Aluminium-plastic film composite layer, preparation method thereof and lithium ion battery

    CN106887537A

  • Preparation method of self-repairing polyurethane adhesive for packaging lithium battery

    CN111690365A

  • Preparation method of electrolyte corrosion resistant aluminum plastic film with fluorine-containing inner surface

    CN114520367A

Cited By

  • High-barrier environment-friendly aluminum foil bag and preparation method thereof

    CN122354009A